What is left unsaid: Omissions in biographical narratives - Correia, S. B.; Caetano, A. (Current Sociology, 2024)
When we ask people to tell us the story of their lives, it is not the full extent of their biographies that we have access to, but only a partial version of it. Biographical narratives are permeated by processes of selection that imply highlighting some things while omitting others. Most of the time, what is left unsaid cannot be fully acknowledged, precisely because it is not explicitly verbalised. In the scope of the research project Biographical echoes, we were able to identify significant events and relationships in a person’s life that were not disclosed in autobiographical accounts but were unveiled in hetero-biographical ones by close people who were interviewed about that person’s life. The triangulation of data allowed us to access elements of a biography that would otherwise have remained unseen. By taking omissions as units of analysis, we characterised their main features and identified three distinct profiles of omissions using a Multiple Correspondence Analysis: relational, light and taboo. We argue that the act of omitting something is a meaningful social action with implications at both the biographical and analytical levels.